Processo alternativo de polarização termo-elétrica de indução e caracterização de não-linearidade de segunda ordem em vidros soda-lime - Moura, André de Lima (2009)
Amorphous materials present macroscopic inversion symmetry. As a consequence, their even order nonlinearities are null. The technological interest in vitreous medium with second order nonlinearity ( χ(2) ) to make photonic devices has stimulated the development of techniques to induce this property. Among them, the thermal-electric field poling is one of the most investigated due its experimental simplicity and results reproducibility. In this work the investigations were directed to the thermal-electric field poling dynamics in soda-lime glasses in view of identify the mainly contributions to the induced nonlinearity stability. Initially were identified the mainly contributions to the induced electrical current. It was observed during the polarizations electroluminescence emission which was shown to be due to ionic displacement and air ionization outside the sample. By using a simplified ionic conduction model was determined two activation energies: ~0,60 and ~3,8eV. The first one, determined from the induced electrical current, was attributed to the sodium conduction; while the second ones, determined by the electroluminescence, attributed to the calcium displacement. Besides the small contribution to the electrical current, the calcium ions, due their small diffusion coefficient, were identified as responsible to the possibility of induce stable second order nonlinearity in soda-lime glasses. Based on these evidences it was used an alternative procedure in which the electrical current flux is controlled. This procedure enabled induce stable χ(2) . This effect was demonstrated to exist 12 months after the polarization procedure, even with a ~50% decrease. The second harmonic generation efficiency was increased in until three times by pumping continuously the polarized samples with infrared radiation from an Nd-YAG laser operating at QSML regime. The threshold applied voltage to observe χ(2) was determined through a modulated applied voltage procedure to be due to the mobility difference between sodium and calcium.